Comparative Analysis of Irrigation Mist and CO2 vs. Direct CO2 Blower in On-Pump Coronary Artery Bypass Grafting Anastomosis: Efficacy, Efficiency, and Fibrillation upon De-Clamping and Micro-Embolic Gas Activity Incidence - Ignazio Condello; Giuseppe Speziale; Flavio Fiore; Giuseppe Nasso (Medicina)
Background and Objectives: In coronary artery bypass grafting (CABG) on pump, achieving optimal visualization is critical for surgical precision and safety. The use of blowers to clear the CABG anastomosis poses risks, including the formation of micro-embolic gas bubbles, which can be insidious and increase the risk of cerebral or myocardial complications. This retrospective study compares the effectiveness of the use of irrigation mist and CO2 versus a direct CO2 blower without irrigation in terms of visualization, postoperative fibrillation, and micro-embolic gas activity. Materials and Methods: The study involved 40 patients who underwent on-pump CABG, with 20 patients assigned to the irrigation mist and CO2 group (ClearView™) and 20 to the direct CO2 blower group. Primary outcomes included the quality of intraoperative visualization, the incidence of fibrillation at aortic de-clamping, and the presence of micro-embolic gas activity detected via transesophageal echocardiography (TEE) in the cardiac chambers. Results: Patients in the irrigation mist and CO2 group experienced superior visualization and reduced tissue desiccation. Fibrillation at the time of aortic de-clamping occurred in two patients (10%) using the irrigation mist and CO2, compared to eight patients (40%) using the direct CO2 blower. Additionally, TEE monitoring revealed lower levels of micro-embolic gas activity in the irrigation mist and CO2 group, indicating a potential reduction in gas embolization risk. Conclusions: The irrigation mist and CO2 system not only provides enhanced visualization during CABG but also significantly reduces the incidence of fibrillation during aortic de-clamping and micro-embolic gas activity. These findings suggest improved patient safety and outcomes, highlighting the irrigation mist and CO2 system as a potentially safer alternative to direct CO2 blowing in the context of myocardial revascularization.